Juvenile social dynamics reflect adult reproductive strategies in bottlenose dolphins. (14th July 2020) - Galezo, Allison A; Foroughirad, Vivienne; Krzyszczyk, Ewa; Frère, Céline H; Mann, Janet
Abstract: The juvenile period is a challenging life-history stage, especially in species with a high degree of fission–fusion dynamics, such as bottlenose dolphins, where maternal protection is virtually absent. Here, we examined how juvenile male and female bottlenose dolphins navigate this vulnerable period. Specifically, we examined their grouping patterns, activity budget, network dynamics, and social associations in the absence of adults. We found that juveniles live in highly dynamic groups, with group composition changing every 10 min on average. Groups were generally segregated by sex, and segregation was driven by same-sex preference rather than opposite-sex avoidance. Juveniles formed strong associations with select individuals, especially kin and same-sex partners, and both sexes formed cliques with their preferred partners. Sex-specific strategies in the juvenile period reflected adult reproductive strategies, in which the exploration of potential social partners may be more important for males (which form long-term alliances in adulthood) than females (which preferentially associate with kin in adulthood). Females spent more time alone and were more focused on foraging than males, but still formed close same-sex associations, especially with kin. Males cast a wider social net than females, with strong same-sex associations and many male associates. Males engaged in more affiliative behavior than females. These results are consistent with the social bonds and skills hypothesis and suggest that delayed sexual maturity in species with relational social complexity may allow individuals to assess potential associates and explore a complex social landscape without the risks associated with sexual maturity (e.g., adult reproductive competition; inbreeding). Abstract : A prolonged juvenile period in socially complex species allows individuals to assess potential mates and social partners without incurring costs associated with sexual maturity. We show that sex differences in the social development of juvenile bottlenose dolphins reflect adult reproductive strategies and that the juvenile period likely prepares individuals for the challenges associated with navigating a complex social landscape as adults. These benefits may mitigate the costs of delayed sexual maturity.